Implementing lung cancer screening: baseline results from a community-based 'Lung Health Check' pilot in deprived areas of Manchester. Issue 4 (13th February 2018) - Crosbie, Phil A; Balata, Haval; Evison, Matthew; Atack, Melanie; Bayliss-Brideaux, Val; Colligan, Denis; Duerden, Rebecca; Eaglesfield, Josephine; Edwards, Timothy; Elton, Peter; Foster, Julie; Greaves, Melanie; et al.
Abstract : We report baseline results of a community-based, targeted, low-dose CT (LDCT) lung cancer screening pilot in deprived areas of Manchester. Ever smokers, aged 55–74 years, were invited to 'lung health checks' (LHCs) next to local shopping centres, with immediate access to LDCT for those at high risk (6-year risk ≥1.51%, PLCOM2012 calculator). 75% of attendees (n=1893/2541) were ranked in the lowest deprivation quintile; 56% were high risk and of 1384 individuals screened, 3% (95% CI 2.3% to 4.1%) had lung cancer (80% early stage) of whom 65% had surgical resection. Taking lung cancer screening into communities, with an LHC approach, is effective and engages populations in deprived areas.